Exploring How Beauty is Perceived: A Comparative Analysis in Uzbek and English (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article delves into the intriguing exploration of the concept of beauty in English and Uzbek languages, offering a comparative analysis of how this fundamental notion is defined and appreciated in two distinct linguistic and cultural contexts. Through an examination of words and phrases used to describe beauty in both languages, the study uncovers the nuances and cultural influences that shape the perception of beauty. While English emphasizes visual aesthetics and physical attractiveness, Uzbek language goes beyond external appearances to include virtues such as inner grace and charm in its definition of beauty. By analyzing these linguistic expressions, the research illuminates the unique cultural perspectives and values that underpin the understanding of beauty in each language, showcasing the diverse ways in which beauty is conceptualized and valued across different cultural landscapes. This comparative analysis not only enriches our understanding of beauty as a universal concept but also highlights the role of language in reflecting and shaping our perceptions of beauty.